Cadaveric variation in the morphology of the gastrocnemius muscle in a Nigerian population - Mamerhi T Enaohwo; Efe J Jaiyeoba-Ojigho; Lilian E Chris-Ozoko; Faith Ogbe; Elohor M Ebijor (Journal of Krishna Institute of Medical Sciences University)
Background: The morphology of the gastrocnemius is typically described as bipennate, with its robustness being a key feature of human locomotion. Aim and Objectives: Although a three-headed variant of the gastrocnemius has been frequently reported, there is limited information on the morphological variability of this muscle in the Nigerian population. Material and Methods: Variations in the heads of origin of the gastrocnemius muscle were examined in 31 lower limbs during routine dissection of the popliteal fossa at the anatomical museum of Delta State University. Results: The most common finding was two heads of origin, present in 80.6% of cases, while 12.9% exhibited a gastrocnemius tertius, and 6.5% had four heads. The plantaris muscle was present in 93.5% of the cadavers, with an absence rate of 6.5%. Conclusion: Awareness of a multi-headed gastrocnemius muscle is crucial when performing myocutaneous flaps around the knee or during limb-sparing surgeries.